2013
DOI: 10.1002/grl.50661
|View full text |Cite
|
Sign up to set email alerts
|

Marine nanogels as a source of atmospheric nanoparticles in the high Arctic

Abstract: The high Arctic (north of 80°N) in summer is a region characterized by clean air and low abundances of preexisting particles. Marine colloidal nanogels i.e., assembled dissolved organic carbohydrate polymer networks have recently been confirmed to be present in both airborne particles and cloud water over the Arctic pack ice area. A novel route to atmospheric nanoparticles that appears to be operative in the high Arctic is suggested. It involves the injection of marine granular nanogels into the air from evapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(104 citation statements)
references
References 43 publications
4
99
1
Order By: Relevance
“…The combination of particle release from droplets together with classical nucleation and growth involving H 2 SO 4 and organic vapours is thus suggested to have been responsible for the NPF event. Indeed, a modelling study carried out by Karl et al (2013) shows good agreement with observed number concentrations, when both nucleation and growth of condensable vapours as well as emissions of marine nanogels are simulated. Most likely, the relative contribution of nucleation and growth by H 2 SO 4 and condensable organic vapours to the observed increase in concentrations in the sub-10 nm size range became greater several hours later, during the early hours of 2 September, when the origin of the incoming air mass shifted to the Beaufort Sea.…”
Section: Period 4: Freeze-up 31 August-2 September (Doy 244-246)mentioning
confidence: 60%
See 3 more Smart Citations
“…The combination of particle release from droplets together with classical nucleation and growth involving H 2 SO 4 and organic vapours is thus suggested to have been responsible for the NPF event. Indeed, a modelling study carried out by Karl et al (2013) shows good agreement with observed number concentrations, when both nucleation and growth of condensable vapours as well as emissions of marine nanogels are simulated. Most likely, the relative contribution of nucleation and growth by H 2 SO 4 and condensable organic vapours to the observed increase in concentrations in the sub-10 nm size range became greater several hours later, during the early hours of 2 September, when the origin of the incoming air mass shifted to the Beaufort Sea.…”
Section: Period 4: Freeze-up 31 August-2 September (Doy 244-246)mentioning
confidence: 60%
“…Via a process involving dissipation of fog/cloud droplets and release and break-up of particles contained within the cloud droplets Bigg, 1999, 2010), the open lead source is suggested to be responsible for the episodic occurrences, such as that during period 3, on 29 August and at ground level during period 4, in the evening on 1 September. However, nucleation and early growth by condensable vapours, such as H 2 SO 4 and organics, are also likely to contribute to the observed NPF event, with a combination of marine gel emissions and nucleation best explaining the observations according to a modeling study (Karl et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In an attempt to explain the characteristics of "colloidal fragmentation" of polymer gels in the high Arctic, a hypothesis has been put forward linking it to evaporation of cloudor fog -droplets by mixing with air, low in moister, at the top and edges of a cloud/fog (Karl et al, 2013;Bigg, 1999, 2010), whereby the colloidal fragments would be released during evaporation.…”
Section: The Relevance Of Polymer Gels For Cloud Activationmentioning
confidence: 99%